Vitamin D status and seroconversion for COVID-19 in UK healthcare workers - Faniyi, Aduragbemi A. (Eur Respir J, 2021)
NHS staff with vitamin D deficiency were more likely to have developed COVID-19, with staff from BAME ethnicity being the most vitamin D deficient https://bit.ly/2J3kVTc